(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
Ater the Civil War of 1936, the Mexican writer and journalist Alfonso Junco was one of the supporters of not only General Franco’s crusades against the republican bloc, but also of the decision of sending them to exile overseas to the “other Spain”, a decision which was carried out ater the conlict. A fervent defender of the cross and a detractor of ideologies such of liberalism, communism and even fascism, Alfonso Junco strongly criticized the arrival of Spanish refugees to Mexico, with the intention of undermining the ideological and institutional project which would end up in forming the Spanish Republican government in exile through the institutional reconstruction of Mexico City in August 1945. Disputes between Indalecio Prieto and Juan Negrín, the Project of Morelia’s children or the confusing issue on the treasures of Vita were topics that intensiied Junco’s criticism against the Spanish in exile.